Encyclopedia of Nanotechnology - Bhushan, Bharat (Springer Netherlands : Imprint: Springer, 2012)
The Encyclopedia of Nanotechnology provides a comprehensive and multi-disciplinary reference to the many fields relevant to the general field of nanotechnology. It aims to be a comprehensive and genuinely international reference work and will be aimed at graduate students, researchers, and practitioners. The Encyclopedia of Nanotechnology introduces a large number of terms, devices and processes which are related to the multi-disciplinary field of Nanotechnology. For each entry in this 4 volume set a 4-10 page description is provided by an expert in the field. Contributions are made by experts from the US, Europe and Asia, making this a comprehensive and truly international Reference Work. The authors are typically from academia, however one quarter of all entries were written by persons from industry. Topics covered in the Reference Work include: - Nano- Microfabrication Processes and Materials for Fabrication - Nanoscale Measurement Techniques <- Nanostructures - Nanomaterials - Nanomechanics - Molecular Modeling and Its Role in Advancing Nanotechnology - MEMS/NEMS - Microfluidics and Nanofluidics - Biomedical Engineering and Biodevices - Bio/Nanotechnology and Nanomedicine - Bio/Nanotechnology for cellular engineering - Drug Delivery - Technology and Applications - Assembly - Organic Electronics - Nano-optical Devices - Micro/nano Integration - Materials, Coatings and Surface Treatments for Nanotribology - Micro/NanoReliability - thermal, mechanical etc. - Biomimetics.